2022
DOI: 10.1177/1357633x221095785
|View full text |Cite
|
Sign up to set email alerts
|

Providing essential gender-affirming telehealth services to transgender youth during COVID-19: A service review

Abstract: The COVID-19 pandemic has had significant effects on service delivery for transgender and gender diverse youth. Many in-person services were suspended in response to the need to follow quarantine and social-distancing guidelines, at both the state and national levels. In response, our pediatric gender clinic adopted a rapid implementation of telehealth services to provide access to gender affirming care. However, there exists little guidance on how to provide gender-affirming care via these platforms. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The study showed how the pandemic brought new forms of stigma to the transgender community, with them being accused of spreading COVID-19. This is in line with literature on trust during pandemics and parallels with South Korea where there was backlash against the LGBTQI + community who were accused of spreading COVID-19 ( 45 , 68 , 69 ). This is in a background of transgender-related stigma which negatively impact mental health for example through higher levels of depression and anxiety ( 70 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study showed how the pandemic brought new forms of stigma to the transgender community, with them being accused of spreading COVID-19. This is in line with literature on trust during pandemics and parallels with South Korea where there was backlash against the LGBTQI + community who were accused of spreading COVID-19 ( 45 , 68 , 69 ). This is in a background of transgender-related stigma which negatively impact mental health for example through higher levels of depression and anxiety ( 70 ).…”
Section: Discussionsupporting
confidence: 89%
“…This was either because of access to GAC being restricted because of pandemic-linked restrictions or because of being advised to do so in the instance of being infected with COVID-19 ( 44 , 46 ). This points to the need to recognize GAC as an essential health service and the need to ensure its continued availability for better mental health of transgender persons, for example, through telehealth services ( 68 , 69 ). This is especially important given that GAC is associated with decreased suicide and anxiety in transgender individuals ( 24 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has also spurred the development of telehealth services that can be further harnessed to improve access to care. For example, McGregor and colleagues (McGregor et al, 2022) report high levels of patient satisfaction and improved appointment attendance with the telehealth model that they developed within the gender program at Boston Children’s Hospital.…”
Section: Impact Of the Sociopolitical Context On Mental Health And We...mentioning
confidence: 99%
“…For example, Grasso et al (2022) found that their US federally qualified gender affirming clinic was able to care for nearly as many new transgender patients from during the first 6 months of the pandemic as they do annually despite the patients hailing from across 24 states. Similarly, another Boston gender‐affirming institution for youth pediatric care converted all in‐person mental health care to telehealth in the first week of the pandemic in March, 2020, thereby minimizing care disruption to their transgender patients and families (McGregor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another Boston gender-affirming institution for youth pediatric care converted all in-person mental health care to telehealth in the first week of the pandemic in March, 2020, thereby minimizing care disruption to their transgender patients and families (McGregor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%